Neuronal Wiskott‐Aldrich syndrome protein regulates Pseudomonas aeruginosa‐induced lung vascular permeability through the modulation of actin cytoskeletal dynamics. Issue 2 (9th January 2020) - Che, Pulin; Wagener, Brant M.; Zhao, Xueke; Brandon, Angela P.; Evans, Cilina A.; Cai, Guo‐Qiang; Zhao, Rui; Xu, Zhi‐Xiang; Han, Xiaosi; Pittet, Jean‐Francois; Ding, Qiang
Abstract: Pulmonary edema associated with increased vascular permeability is a severe complication of Pseudomonas (P.) aeruginosa ‐induced acute lung injury. The mechanisms underlying P aeruginosa ‐induced vascular permeability are not well understood. In the present study, we investigated the role of neuronal Wiskott Aldrich syndrome protein (N‐WASP) in modulating P aeruginosa‐ induced vascular permeability. Using lung microvascular endothelial and alveolar epithelial cells, we demonstrated that N‐WASP downregulation attenuated P aeruginosa ‐induced actin stress fiber formation and prevented paracellular permeability. P aeruginosa ‐induced dissociation between VE‐cadherin and β‐catenin, but increased association between N‐WASP and VE‐cadherin, suggesting a role for N‐WASP in promoting P aeruginosa ‐induced adherens junction rupture. P aeruginosa increased N‐WASP‐Y256 phosphorylation, which required the activation of Rho GTPase and focal adhesion kinase. Increased N‐WASP‐Y256 phosphorylation promotes N‐WASP and integrin αVβ6 association as well as TGF‐β‐mediated permeability across alveolar epithelial cells. Inhibition of N‐WASP‐Y256 phosphorylation by N‐WASP‐Y256F overexpression blocked N‐WASP effects in P aeruginosa‐ induced actin stress fiber formation and increased paracellular permeability. In vivo, N‐WASP knockdown attenuated the development of pulmonary edema and improved survival in a mouse model of P aeruginosa pneumonia. Together, our data demonstrate that N‐WASP plays an essential role in P aeruginosa ‐induced vascular permeability and pulmonary edema through the modulation of actin cytoskeleton dynamics.